2010
DOI: 10.1177/0300985810375240
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Metabolism and Rickets in Domestic Animals

Abstract: Rickets and osteomalacia are increasing in prevalence in people because of cultural practices, breast-feeding, decreased sun exposure, and increased sunscreen usage. Several hereditary forms of rickets owing to either renal phosphate wasting or defects in vitamin D metabolism are also reported in people. Rickets is well recognized in domestic animals, but published reports are not always supported by microscopic findings, and diagnoses based on clinical signs and radiology are unreliable. Most cases in domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 216 publications
(384 reference statements)
2
161
0
3
Order By: Relevance
“…Substantial work is required to determine if the phosphatonin pathways of veterinary species are similar to those in humans; certainly, we know that there are differences in vitamin D metabolism, 42 and so it stands to reason that given evolutionary adaptation, differences may also occur in the phosphatonin system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial work is required to determine if the phosphatonin pathways of veterinary species are similar to those in humans; certainly, we know that there are differences in vitamin D metabolism, 42 and so it stands to reason that given evolutionary adaptation, differences may also occur in the phosphatonin system.…”
Section: Resultsmentioning
confidence: 99%
“…3 Rickets and osteomalacia are syndromes of deficient calcium and phosphorus deposition in osteoid during bone synthesis. 42 Failure of normal mineralization in the physeal or articular cartilage of children leads to rickets, characterized by thickening and flaring of physes, bowing of long bones, bone and joint pain, delayed growth, delayed standing or walking, frequent falling, and even seizures due to hypocalcemia. 188,206 Osteomalacia is observed in adults and leads to more occult signs such as bone pain, gait instability, muscle weakness, and pathological fractures.…”
Section: Fibroblast Growth Factor 23-disease In Humans and Lessons Frmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown in the investigations that vitamin D is closely related to calcium and phosphor homeostasis, and plays a significant role in the bone model formation (Dittmer and Thompson 2011). In the study of Driel et al (2006) conducted in order to investigate the autocrine/paracrine function of 1α, 25-OH-D 3 , it was determined that 1α-hy-droxylase is expressed in the human osteoblasts, and also there are megalin and cubilin protein receptors bound to vitamin D. It was observed that osteoblasts produced 1α, 25-(OH)2D 3 , and ALP and osteocalcin expressions increased mildly with the addition of 25-OH-D 3 as a substrate to the osteoblast cell cultures while it did not have any effect on Ca and parathyroid hormone regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The main activation stage in the vitamin D metabolism takes place in the kidneys and is catalyzed by 25-hydroxycalciferol--1α-hydroxylase. 1,25 dihydroxycholecalciferol (1,25 dihydroxyvitamin D) formed as a result of this hydroxylation is the most active form of vitamin D and it is responsible for all the effects of vitamin D (Gow et al 2011, Dittmer andThompson 2011).…”
Section: Introductionmentioning
confidence: 99%